2019
DOI: 10.1002/ijc.32167
|View full text |Cite
|
Sign up to set email alerts
|

TRIM28 haploinsufficiency predisposes to Wilms tumor

Abstract: Two percent of patients with Wilms tumors have a positive family history. In many of these cases the genetic cause remains unresolved. By applying germline exome sequencing in two families with two affected individuals with Wilms tumors, we identified truncating mutations in TRIM28. Subsequent mutational screening of germline and tumor DNA of 269 children affected by Wilms tumor was performed, and revealed seven additional individuals with germline truncating mutations, and one individual with a somatic trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 45 publications
0
65
2
Order By: Relevance
“…In recent decades, genetic testing techniques have evolved substantially with comprehensive next‐generation sequencing initiatives identifying additional genes of interest in larger numbers of oncology patients. Through these studies, pathogenic alterations in novel genes have been identified in patients with WT including CTR9 , TRIM28 , and REST . Although sequencing initiatives are becoming increasingly accessible in large academic institutions (often on a research basis), the majority of practitioners do not have access to these resources and rely on clinical judgment and targeted molecular diagnostic technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, genetic testing techniques have evolved substantially with comprehensive next‐generation sequencing initiatives identifying additional genes of interest in larger numbers of oncology patients. Through these studies, pathogenic alterations in novel genes have been identified in patients with WT including CTR9 , TRIM28 , and REST . Although sequencing initiatives are becoming increasingly accessible in large academic institutions (often on a research basis), the majority of practitioners do not have access to these resources and rely on clinical judgment and targeted molecular diagnostic technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Through these studies, pathogenic alterations in novel genes have been identified in patients with WT including CTR9, TRIM28, and REST. [10][11][12][13] Although sequencing initiatives are becoming increasingly accessible in large academic institutions (often on a research basis), the majority of practitioners do not have access to these resources and rely on clinical judgment and targeted molecular diagnostic technologies. Despite this, CPS identification is becoming more challenging for clinicians with expanding phenotypic diversity as well as a growing spectrum of associated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The field of hereditary cancer predisposition and genetic testing is rapidly evolving and various new susceptibility genes and interactions will be discovered in the near future . As a consequence, today's genetic test results will be outdated within a few years.…”
Section: Diagnosing Cps In Children and Adolescents With Cancermentioning
confidence: 99%
“…Thus, even more children may be affected by monogenic CPSs due to additional pathogenic variants in previously unrecognized susceptibility genes. More complex traits, involving cooperative effects of two or more variants in different genes of the same or concurring signaling pathways, and polygenic risk scores have to be considered . Recently, Waszak et al demonstrated that the number of adults affected by genetic cancer predisposition may increase by an additional 10% if mutations in DNA‐repair genes are considered, adding up to an incidence in total of approximately 20% …”
Section: Introductionmentioning
confidence: 99%
“…Genetic characterization already allows further subclassification of epithelial tumors. TRIM28 inactivation as a driver of epithelial‐type WTs, often already present as a heterozygous germline mutation, clearly defines a specific molecular subgroup among those with an earlier onset . Thus, the 3 cases with bilateral WTs will have a high chance to be explainable by a TRIM28 germline predisposition.…”
mentioning
confidence: 99%